Awareness of Dental Undergraduates, Post Graduates and Dental Practitioners' about Dental and Biomedical Waste Management - Kamran, Muhammad Abdullah; Zareef, Uzma; Ahmed, Tauseef; Rasool, Raffat; Khan, Nabeel; Kashif, Mehwash (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: To assess undergraduate, postgraduate dental students' and dental practitioners' knowledge of management of dental and biomedical waste and to focus on critical issues such as environment-friendly waste management. Methodology: A total of 273 participants were recruited from January to June 2019 through convenience sampling in this cross-sectional study; undergraduate, postgraduate dental students, and general dental practitioners from private and public sector dental colleges of Karachi. The respondents answered different categories of waste management, including biomedical waste rules, waste disposal measures, dental waste types, common dangers of improper waste management, and some particular equipment problems, data analyzed on SPSS version 17.00. Results: From 273 (92.8%) completed questionnaires, 217(79.4%) were females. Undergraduate students were 61.9%, (n=169). Almost 64.4 % (n=176) of respondents didn't know about dental waste management rules. Among 75 % (n=205) of respondents, there was a consensus that qualified professionals should treat hospital disposal. Only 67.7% (n= 185) of individuals surveyed stated that they were familiar with the categories formed by dental waste. Approximately 95.5% (n=260) of respondents recommend workshops and Continues medical education seminars for waste management. Compared to undergraduate students, postgraduate students had a significantly higher mean score, decreasing the "know-do gap" (p=0.069). Conclusion: Among undergraduate dental students and dental practitioners, postgraduates were found to have a greater understanding of the correct methods for disposing of healthcare waste. However, the overall knowledge level of environment friendly waste management was insufficient. Keywords: Disposal of medical waste; Understanding of health, attitudes, practice; Dentistry